Institutional pressures, green logistics activities and efficiency performance: a survey with logistics service providers in Brazil (2024)
The objective of this research is to verify the relationship between institutional pressures, green logistics activities and impacts on logistics performance. A survey of 56 logistics service providers was conducted. In relation to the data acquired, the return of 138 questionnaires answered by the middle/tactical managers of the 56 logistics service providers in Brazil was received. Institutional pressures were the antecedents capable of explaining the corresponding variation in the green logistics construct (green packaging) in R2=0.3750, green logistics (green transport) in R2=0.3909 and green logistics (green warehousing and buildings) in R2=0.0389. Similarly, all green logistics constructs were able to explain the variation corresponding to a value observed in R2=0.5442 referring to efficiency performance (costs). The results demonstrate the influence of institutional pressures on green logistics activities as well as the impact of green logistics on efficiency performance (costs).